The Languages Spoken in the Water Body (or the Biological Role of Cyanobacterial Toxins) - Kaplan, Aaron; Harel, Moshe; Kaplan-Levy, Ruth N.; Hadas, Ora; Sukenik, Assaf; Dittmann, Elke (Frontiers in Microbiology, 2012)
Although intensification of toxic cyanobacterial blooms over the last decade is a matter of growing concern due to bloom impact on water quality, the biological role of most of the toxins produced is not known. In this critical review we focus primarily on the biological role of two toxins, microcystins and cylindrospermopsin, in inter- and intra-species communication and in nutrient acquisition. We examine the experimental evidence supporting some of the dogmas in the field and raise several open questions to be dealt with in future research. We do not discuss the health and environmental implications of toxin presence in the water body.